Parenting Socialization: Efforts to Provide Parent Training at Bimbingan Belajar Ceria Karawaci , Tangerang - Jossapat Hendra Prijanto; Juliana Tirza (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2020)
Home care and education at school are important pillars of child development. Economic conditions, geographical position, educational background of parents, and the stigma that develops in society towards women who do not need to be highly educated have a significant effect on parenting patterns, especially mother-to-child care. In fact, not all Indonesian children receive proper care. Data from the National Service Agency (KOMNAS) for Children in 2006 showed that there were still 1,124 violence against children, 433 children experienced physical violence and 106 experienced psychological violence. Various bad facts about the concern for Indonesian children have encouraged UPH Lecturers to contribute in community service to provide training for parents of students at Bimbingan Belajar Ceria Karawaci , Tangerang. They come from families with low levels of education and difficulties. It is hoped that this training activity can provide insight into their parents and have an impact on the mindset of the community around Bimbingan Belajar Ceria regarding proper parenting for their children. Various efforts were made in community service in Bimbingan Belajar Ceria, stated in this paper. This paper aims to share awareness about the parental training efforts that have been carried out by Pelita Harapan University lecturers, with the hope of forming a smart and stable society. The result of this community service are the parents get many parental skills and the feedback are positive even they want this program to be continued and give more knowledge for them. Keywords: parenting, community service, education